SCM Strategy for Sales Augmentation using TSP Algorithm and Time Bound Marginal Discount Utility - Sandeep Mathur; Varinder Kumar Mittal; Nitin Upadheye; Kshitij Mathur (International Journal of Supply Chain Management, 2018)
At present, Fast Moving Electrical Goods (FMEG) industries target wholesale dealers and not the retailers for supplying their finished goods. The reasons for this being: a) Dealers are fewer in numbers and hence net distance travelled per shipment is less b) Dealers tend to demand higher lot sizes, thereby decreasing overall cost of transportation per unit for the product. This work presents a supply chain strategy to use retailer based distribution by solving both the issues by a) using the concept of milk runs by taking analogy of Travelling Salesman Problem to decrease transportation cost and b) applying time bound marginal discount utility to solve the issue of low lot sizes. A case study has been prepared based on field experiences of middle level FMEG industry for its four popular consumer products. It presents application of travelling salesman problem (TSP) algorithm to make efficient milk runs. Also, concept of time bound marginal discount utility solution is proposed to find an optimum discount price to optimize the transportation cost and revenues. The paper compares this proposed supply chain strategy with manufacturer to dealer model and manufacturer to retailer model with various combinations.